2007
DOI: 10.1186/1478-4505-5-1
|View full text |Cite
|
Sign up to set email alerts
|

What did the public think of health services reform in Bangladesh? Three national community-based surveys 1999–2003

Abstract: BackgroundSupported by development partners, the Government of Bangladesh carried out a comprehensive reform of health services in Bangladesh between 1998 and 2003, intended to make services more responsive to public needs: the Health and Population Sector Programme (HPSP). They commissioned a series of surveys of the public, as part of evaluation of the HPSP. This article uses the survey findings to examine the changes in public opinions, use and experience of health services in the period of the HPSP.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 15 publications
4
71
0
Order By: Relevance
“…Note: FGD: Focus Group Discussion results of our previous quantitative studies and are also consistent with other studies [1,8]. With the exception of corruption, intersector authoritative gaps and moral issues, no notable new issues emerged; however, the insights in this regard were deepened.…”
Section: Fgd1 Fgd2 Fgd5supporting
confidence: 88%
See 1 more Smart Citation
“…Note: FGD: Focus Group Discussion results of our previous quantitative studies and are also consistent with other studies [1,8]. With the exception of corruption, intersector authoritative gaps and moral issues, no notable new issues emerged; however, the insights in this regard were deepened.…”
Section: Fgd1 Fgd2 Fgd5supporting
confidence: 88%
“…Many poor patients visit unqualified doctors before they come to qualified doctors [8]. Because of this, they already are unhappy because of monetary loss and ineffective treatment and good prognosis with qualified treatment is often not enough to satisfy them because of the mental and economic adversity they suffer.…”
Section: Addressing Patients' Satisfaction Dynamics In the Public Andmentioning
confidence: 99%
“…Recent studies on health-seeking behaviour of the poor and disadvantaged populations (such as the ultra-poor consuming <1805 kcal per capita per day, ethnic minorities, elderly, women) in rural Bangladesh revealed that the unqualified practitioners are the major providers of health care for these populations [8,[14][15][16]. This varies from 40 to 60% in different Table 1 Socio-economic and demographic characteristics of the unqualified/semi-qualified health care providers (%) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cockcroft et al, 2007;Cockcroft et al, 2011). With the exception of corruption, inter-sector authoritative gaps and moral issues, no notable new issues emerged; however, the insights in this regard were deepened.…”
Section: Discussionmentioning
confidence: 99%